2016
DOI: 10.2320/matertrans.m2016044
|View full text |Cite
|
Sign up to set email alerts
|

Change in Microstructure, Mechanical Strength and Corrosion Resistance of Ti-8Mo-xNi Alloys through Various Sintering Temperatures

Abstract: In this study, three different powders are mixed and used to produce Ti-8Mo-xNi alloys in three different proportions: Ti-8Mo-4Ni, Ti8Mo-6Ni and Ti-8Mo-8Ni. The Ti-Mo-Ni alloys simultaneously undergo various vacuum sintering temperatures of 1125, 1150, 1175 and 1200 C, respectively. The experimental results show that the Ti-8Mo-8Ni alloys acquire a higher sintering density (98.9%) and hardness (52.1 HRC) after sintering at 1175 C for 1 h. However, due to the grain growth and increased amount of nickel in the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…5a. The previous literature indicates that decreasing the porosities and increasing the density of sintered materials effectively enhances plastic deformation resistance and hardness [2,12]. In this study, the porosities decreased and the relative density increased as the sintering temperature was raised (1175 → 1225 → 1275°C), which could be the main factor in improving hardness.…”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…5a. The previous literature indicates that decreasing the porosities and increasing the density of sintered materials effectively enhances plastic deformation resistance and hardness [2,12]. In this study, the porosities decreased and the relative density increased as the sintering temperature was raised (1175 → 1225 → 1275°C), which could be the main factor in improving hardness.…”
Section: Resultsmentioning
confidence: 62%
“…Fig 2 reveals the XRD patterns of the NbC-1, NbC-3 and NbC-5 specimens after sintering at 1275°C for 1 h. Previous study indicated that the impurity concentrations of vacuum-sintered commercially pure titanium with fine grains were sufficiently low to meet the ASTM standard. It illustrates that the oxygen, nitrogen and hydrogen contents of the specimens was lower than that of ASTM (B381-10) [2,11]. As a result, the contamination levels such as oxygen, nitrogen and hydrogen can be ignored.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations